Parate Execution Secured Assets of Bad Credit In Indonesian Banking System - Januar Agung Saputera; Djuhaendah Hasan; Zulkarnain Sitompul; Ahmad Muliadi (The Southeast Asia Law Journal, 2015)
Parate execution carried out by the bank as a repayment on credit cus- tomers are executions carried out solely by the holder of a security in- terest (the bank) without the assistance or intervention of the District Court, but directly through the Office of State Auction. In the execution of the auction debtors seek legal shortcomings with the proposition less sense of fairness. To analyze the problem is to use a grand theory of the welfare state, middle range theory legal justice and applied theory of development, because who wants to be resolved how the relationship between banks and customers to jointly provide welfare are not detri- mental to either side, as well as on the legal certainty guaranteed by the legislation in carrying out the execution parate to the bank and ftnd the concept of law in the resolution of bad loans for the purpose of legal development in the future. The Research method is normative legal research, to obtain the necessary data in connection with the period is- sues. The data used secondary data. Data analysis be done with juridical analysis of qualitative. From the research results can be obtained dispute bad credit not provide legal justice and certainty for creditors as they occur rejection of the auction by KPKNL result of the conftscation of the object of mortgage.